2017
DOI: 10.2147/ijn.s140939
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory activity of selenium nanoparticles functionalized with oseltamivir on H1N1 influenza virus

Abstract: As an effective antiviral agent, the clinical application of oseltamivir (OTV) is limited by the appearance of drug-resistant viruses. Due to their low toxicity and excellent activity, the antiviral capabilities of selenium nanoparticles (SeNPs) has attracted increasing attention in recent years. To overcome the limitation of drug resistance, the use of modified NPs with biologics to explore novel anti-influenza drugs is developing rapidly. In this study, OTV surface-modified SeNPs with superior antiviral prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
94
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 136 publications
(97 citation statements)
references
References 47 publications
1
94
0
2
Order By: Relevance
“…Li et al demonstrated this strategy of H1N1 viral inhibition using oseltamivir (OTV) decorated SeNPs (Se@OTV). 134 This strategy could be effectively evaluated in vitro in case of NiV inhibition. Likewise modulation of viral transcription using MWCTs-ribavirin by Zhu et al, 135 targeted binding on conservative regions on viral genome using TiO 2 NPs and polylysine (PL)containing oligonucleotides nanocomposite by Levina et al 136 and silencing viral replication with the help of solid lipid NPs by Torrecilla et al 137 etc.…”
Section: Possible Nano-based Approach For Niv Inhibitionmentioning
confidence: 99%
“…Li et al demonstrated this strategy of H1N1 viral inhibition using oseltamivir (OTV) decorated SeNPs (Se@OTV). 134 This strategy could be effectively evaluated in vitro in case of NiV inhibition. Likewise modulation of viral transcription using MWCTs-ribavirin by Zhu et al, 135 targeted binding on conservative regions on viral genome using TiO 2 NPs and polylysine (PL)containing oligonucleotides nanocomposite by Levina et al 136 and silencing viral replication with the help of solid lipid NPs by Torrecilla et al 137 etc.…”
Section: Possible Nano-based Approach For Niv Inhibitionmentioning
confidence: 99%
“…Selenium nanoparticles (SeNPs) was fabricated according to previous studies (Li et al, 2017). In brief, 1 mM vitamin C (Vc) solution, 0.2 M Na 2 SeO 3 solution, and 1.5 mg/mL RGDfC solution were freshly prepared.…”
Section: Fabrication and Characterizations Of Nanoparticlementioning
confidence: 99%
“…Wang et al [17] reported that the broad spectrum antiviral polyoxometalate may become a novel antiviral drug. In our previous research, selenium nanoparticles (SeNPs) have been proven to exhibit significant antiviral activity [18,19]. Selenium as an essential trace element control some key biological processes containing specific enzyme modulation and reactive oxygen species (ROS) elimination [19].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous research, selenium nanoparticles (SeNPs) have been proven to exhibit significant antiviral activity [18,19]. Selenium as an essential trace element control some key biological processes containing specific enzyme modulation and reactive oxygen species (ROS) elimination [19]. A deficiency in selenium could cause susceptibility to the virus infection [20].…”
Section: Introductionmentioning
confidence: 99%